2003
DOI: 10.1097/00132578-200307000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless Cataract Surgery With Nucleus Extraction: Outcome of a Prospective Study in Nepal

Abstract: Aim: To report the short and medium term outcome of a prospective series of sutureless manual extracapsular cataract extractions (ECCE) at a high volume surgical centre in Nepal. Methods: Cataract surgery was carried out, on eyes with no co-existing diseases, in 500 consecutive patients who were likely to return for follow up. The technique involved sclerocorneal tunnel, capsulotomy, hydrodissection, nucleus extraction with a bent needle tip hook, and posterior chamber intraocular lens (PC-IOL) implantation ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 7 publications
4
37
0
Order By: Relevance
“…Phacoemulsification machine is not required in MSICS in which nucleus is removed through a 6.5‐mm sclerocorneal tunnel. Several centres have reported success with MSICS (Hennig et al. 2003; Venkatesh et al.…”
Section: Introductionmentioning
confidence: 99%
“…Phacoemulsification machine is not required in MSICS in which nucleus is removed through a 6.5‐mm sclerocorneal tunnel. Several centres have reported success with MSICS (Hennig et al. 2003; Venkatesh et al.…”
Section: Introductionmentioning
confidence: 99%
“…7 Some recent studies of high volume cataract surgery in India and Nepal report good results. [8][9][10][11][12][13][14] In order to investigate whether high volume surgeries can be performed routinely, without compromising quality, we retrospectively reviewed the results of 593 surgeries performed by three experienced surgeons, achieving surgical times of 3.75 minutes/case (16-18 cases/hour), utilising the technique of manual small incision cataract surgery (manual SICS).…”
mentioning
confidence: 99%
“…[1][2][3] Hennig et al, 4 found that visual acuity improved to 6/18 or better in 96.2% of eyes after 6 weeks and 95% after 1 year after small incision cataract surgery (SICS) and posterior chamber intraocular lens implantation (PC-IOL) implantation.…”
Section: Introductionmentioning
confidence: 99%